Comparison Results on Preconditioned GAOR Methods for Weighted Linear Least Squares Problems - Guangbin Wang; Yanli Du; Fuping Tan (Journal of Applied Mathematics)
We present preconditioned generalized accelerated overrelaxation methods for solving weighted linear least square problems. We compare the spectral radii of the iteration matrices of the preconditioned and the original methods. The comparison results show that the preconditioned GAOR methods converge faster than the GAOR method whenever the GAOR method is convergent. Finally, we give a numerical example to confirm our theoretical results.